Waterfowl censuses on the Mississippi river from St. Louis, Missouri to Cairo, Illinois, and on the lower Kaskaskia river, Illinois: 14 October 1984 through 24 April 1985 - Sanderson, Glen C. (INHS Section of Wildlife Research, 1985)
Made available in DSpace on 2009-03-30T17:18:36Z (GMT). No. of bitstreams: 3 inhsswrv01985i0000a_tei.xml: 153783 bytes, checksum: 8906f34331739677455d4641789068e8 (MD5) inhsswrv01985i0000a_opt.pdf: 5464166 bytes, checksum: 43aa68b438fdc5de7682ace6d53a0766 (MD5) license.txt: 4890 bytes, checksum: 6185bd8c4fe743eb0de86f7713779247 (MD5) Previous issue date: 1985 US Army Corps of Engineers St. Louis District, Purchase order no. DACW43-85-M-0659